دور مشعر ريد بتنظير عنق الرحم في التنبؤ بآفات عنق الرحم (مجلة جامعة اللاذقية - سلسلة العلوم الصحية, 2019)
The aim of study was knowledge of ability of reid colposcopic index to detection of cervix lesions. Materials and methods: The research was conducted in the department of obestetric and gynecology at Tishreen university hospital in Latakia in the period between (1/3/2018) and (1/2/2019). The study included 120 patients who check out the gynecological clinic, they submitted to colposcopy and papanicolau smear to evaluate the role of reid colposcopic index in detection of cervix lesions. The results: the rate of benign pap smears was 91.6%, while the rate of benign cases was 30% according to the reid scoring system. The sensitivity of colposcopic reid index was 100%, the specificity was 32.7%, the positive predictional value was 7.14%, while the negative predictional value was 100%. There was no relation between the finding of colposcopy using reid colposcopic index and old of patient (p=0.05 =0.05). There was no relation between the finding of colposcopy using reid colposcopic index and number of gravity (p =0.4>0.05). There was no relation between the finding of colposcopy using reid colposcopic index and kind of epithelium of cervix (p=0.05 =0.05). There was difference between reid colposcopic index and pap nicolau.   هدف البحث: معرفة أو كشف قدرة مشعر ريد بتنظير عنق الرحم المكبر على كشف آفات عنق الرحم. المواد والطرق: أجري البحث في قسم التوليد وأمراض النساء في مشفى تشرين الجامعي في الفترةالواقعة بين (1/3/2018) و(1/2/2019). شمل البحث 120 مريضة من مراجعات العيادة النسائية، أجري لهن تنظير عنق الرحم المكبر باستخدام مشعر ريد، ولطاخة بابانيكولاو، وذلك لتقييم دور مشعر ريد بتنظير عنق الرحم المكبر في التنبؤ بآفات عنق الرحم. النتائج: كانت نسبة الحالات السليمة بحسب الموجودات الخلوية91.6 %، بينما كانت حسب مشعر ريد 30%، كما كانت حساسية التنظير حسب مشعر ريد مقابل الموجودات الخلوية (Gold Standard) 100%، ونوعية التنظير حسب مشعر ريد مقابل الموجودات الخلوية (Gold Standard) كانت32.7.% v       حساسية التنظير حسب مشعر ريد مقابل الموجودات الخلوية (Gold Standard) كانت 100% v       نوعية التنظير حسب مشعر ريد مقابل الموجودات الخلوية (Gold Standard) كانت32.7%. v       القيمة التنبؤية الايجابية للاختبار PPV=7.14 %، والقيمة التنبؤية السلبية للاختبار NPV=100 % v       لا وجود علاقة بين الموجودات على تنظير عنق الرحم حسب مشعر ريد وعمر المريضة p=0.05=0.05. v       لا وجود علاقة بين الموجودات على تنظير عنق الرحم حسب مشعر ريد وعددالولاداتp=0.4>0.05. v       لا وجود علاقة بين نوع بشرة عنق الرحم والموجودات على تنظير عنق الرحم حسب مشعر ريدp=0.05=0.05. وهكذا نستنتج وجود اختلاف بين مشعر ريد ولطاخة بابا نيكولاو.